PREDICTORY VALUE OF A BATTERY OF MOTOR TESTS WITH REFERENCE TO SHORT-DISTANCE AND LONG-DISTANCE RUNNING - Naser Rashiti; Fadil Nika; Blerim Sylejmani (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The research is conducted in order to determine the impact of five (5) motor tests (predictory system) applied on two motor criterion variables (tests). The entity sample consists of 173 schoolchildred in fourth grade from school "Zenel Hajdini" in Gnjilane. The sample is divided in two subsamples regarding the sex of the schoolchildren. The criterion variables are applied as follows: for the male entities a 100-meter and a 1000-meter running is required, and for the female entities a 100-meter and a 800-meter running is required. According to the data obtained the predictory system of the applied motor tests, it is determined that statistically significant impact is achieved in the variable of a 1000-meter running with the schoolboys only